Increased expression of heat shock factor 1 (HSF1) is associated with poor survival in gastric cancer patients - Weigang Dai; Jinning Ye; Zhimei Zhang; Liang Yang; Hui Ren; Hui Wu; Jianhui Chen; Jieyi Ma; Ertao Zhai; Shirong Cai; Yulong He (BMC, 2018)
Abstract Background Heat shock factor 1 (HSF1) was initially identified as a transcription factor encoding heat shock proteins, which assist in refolding or degrading damaged proteins. Recent studies have reported that HSF1 can act as an oncogene that regulates tumour progression. The present study aimed to elucidate the clinicopathological significance and prognostic value of HSF1 expression in gastric cancer (GC). Methods The data from The Cancer Genome Atlas (TCGA) were used to analyse HSF1 expression in GC and normal tissues, while 8 pairs of freshly frozen tissue samples were used to investigate HSF1 expression at the mRNA and protein levels in GC tissues and adjacent normal tissues using quantitative real-time polymerase chain reaction (qRT-PCR) and western blotting assays. The correlations between HSF1 expression and clinicopathological parameters, including the survival rate, were investigated in 117 GC tissue samples by immunohistochemical analysis. Results The results of bioinformatics analysis, qRT-PCR, and western blot showed that HSF1 expression was higher in GC tissues than in normal tissues. High HSF1 expression was found in 54.7% (64/117) patients. Patients with high HSF1 expression had larger tumour size (P = 0.001), advanced Bornmann classification (P = 0.002), advanced depth of invasion (P = 0.015), lymph node metastasis (P<0.001), distant metastasis (P = 0.011) and tumour-node-metastasis (P<0.001). Moreover, the Kaplan-Meier and Cox proportional hazards analyses indicated that high HSF1 expression was significantly associated with poor overall survival and recurrence-free survival in GC patients and that high HSF1 expression was an independent prognostic factor for the long-term survival in GC patients. Conclusions Taken together, our results show that high HSF1 expression is significantly correlated with advanced tumour progression and poor prognosis. In addition, HSF1 expression can serve as a biomarker for the prognosis of patients with GC.